Vaquita and Other Stories - Pearlman, Edith, 1936- (Book collections on Project MUSE., 1996)
Fifteen stories. They include The Cook, which deals with abandoned children being used as donors for body organs, and To Reach This Season, in which a homosexual adopts a boy from the Third World.